2017
DOI: 10.18632/oncotarget.20455
|View full text |Cite|
|
Sign up to set email alerts
|

CUL4B promotes bladder cancer metastasis and induces epithelial-to-mesenchymal transition by activating the Wnt/β-catenin signaling pathway

Abstract: Increased expression of cullin 4B (CUL4B) is linked to progression in several cancers. This study aims to explore the effects of CUL4B on bladder cancer (BC) metastasis and epithelial-to-mesenchymal transition (EMT) and potential correlation to the Wnt/β-catenin signaling pathway. We collected BC tissues and adjacent normal tissues from 124 BC patients. Quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting were employed in order to detect the expression of Wnt/β-catenin signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
0
23
0
2
Order By: Relevance
“…The involvement of Wnt/β-catenin signalling in a wide variety of cellular processes, such as growth, differentiation, invasion and tumourigenesis (47), has been well documented. Our data, along with those of others, have revealed CUL4B to be a positive regulator of the Wnt/β-catenin pathway (9,48). In this study, based on our finding that the behaviour of GC cells was affected by miR-381, miR-489 and CUL4B expression, we examined whether the Wnt/β-catenin pathway was also involved in this interplay.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The involvement of Wnt/β-catenin signalling in a wide variety of cellular processes, such as growth, differentiation, invasion and tumourigenesis (47), has been well documented. Our data, along with those of others, have revealed CUL4B to be a positive regulator of the Wnt/β-catenin pathway (9,48). In this study, based on our finding that the behaviour of GC cells was affected by miR-381, miR-489 and CUL4B expression, we examined whether the Wnt/β-catenin pathway was also involved in this interplay.…”
Section: Discussionmentioning
confidence: 58%
“…Cullin 4B (CUL4B) is a scaffold protein responsible for assembling DDB1, RBX1 and substrate component to form the CRL4B ubiquitin ligase complexes (3), contributing to ubiquitin-mediated proteolysis and tumourigenesis (4,5). Mounting evidence has highlighted the upregulation and oncogenic potential of CUL4B in various types of cancer, including hepatocellular carcinoma, lung cancer, colon cancer and bladder cancer (6)(7)(8)(9)(10). Mechanistically, CUL4B epigenetically represses a series of tumour suppressors, including insulin-like growth factor-binding protein 3 (IGFBP3), phosphatase and tensin homolog (PTEN) and p16 through physical interaction with the SIN3A/HDAC and SUV39H1/HP1/DNMT3A complexes (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Schmitz-drager et al investigated a total of 185 paraffin-embedded bladder cancer tissue specimens immunohistochemically for the overexpression of c-myc (31). Mao et al reported that activation of the Wnt/β-catenin signalling pathway induced epithelial-mesenchymal transition and promote bladder cancer metastasis (34). In addition, the Wnt signalling has been suggested as a molecular target for bladder cancer (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, silencing of CUL4B is also involved in cell growth. Different cell experiments had confirmed that CUL4B activates the expression of mRNA and protein levels of c-Myc, promoting Wnt/β-catenin signaling activation and tumor progression ultimately [40,41]. Investigation of DLBCL consistently illustrated the connection between Ki-67, c-Myc and aggressive clinical behavior [42][43][44].…”
Section: Discussionmentioning
confidence: 99%